Restorative Justice versus Retributive Justice: Exploring Child Abuse Cases in Indonesia - muhammad havez (Universitas Katolik Indonesia Atma Jaya, 2026)
Law enforcement of child abuse cases in Indonesia presents complex challenges, particularly in determining the most effective justice approach for both victims and perpetrators. This article compares Restorative Justice and Retributive Justice in handling child abuse cases, focusing on their impact on victim rehabilitation, deterrent effects on perpetrators, and protection for victims. Restorative Justice, which focuses on restoring relationships between victims and perpetrators, can accelerate the rehabilitation process and reduce long-term trauma for victims. Conversely, Retributive Justice, which prioritizes punishment for perpetrators and aims to provide a deterrent effect, often neglects the aspect of recovery for victims. This article also explores the social and psychological impacts experienced by victims depending on the approach used, as well as the challenges faced by the Indonesian legal system in effectively implementing Restorative Justice in child abuse cases. By understanding these two approaches, it is hoped that more comprehensive solutions can be found in handling child abuse cases in Indonesia.